Ser diferente, ¿suficiente para la exclusión? - Alfaro Piña, Jimmy Armando (2012)
Social discrimination is one of the many aspects that characterize a society, and limits equal development for individuals who one way or another are different. The ideology of a patriarchal society, stereotypes promoted by the media, old-fashioned ideas of Christianity and the lack of sexual education, have promoted discrimination against homosexual people, which is dominated by a surface image and as could be loaded with myths and stereotypes or sick depraved character.